2020
DOI: 10.1136/bmjopen-2020-037905
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective cross-sectional analysis of the changes in marijuana use in the USA, 2005–2018

Abstract: ObjectivesUnderstanding trends of marijuana use in the USA throughout a period of particularly high adoption of marijuana-legalisation, and understanding demographics most at risk of use, is important in evolving healthcare policy and intervention. This study analyses the demographic-specific changes in the prevalence of marijuana use in the USA between 2005 and 2018.Design, setting and participantsA 14-year retrospective cross-sectional analysis of the National Health and Nutrition Examination Survey database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…11 The information collected was designed to assess the incidence of major diseases and disease risk factors to promote health and prevent diseases. 12 Participants who did not have depression questionnaire data or sleep disorder data, or lack other information were excluded. This study did not need to be approved by the Institutional Review Board of the Affiliated Hospital of North Sichuan Medical College because the data was accessed from the NHANES (a publicly available database).…”
Section: Methodsmentioning
confidence: 99%
“…11 The information collected was designed to assess the incidence of major diseases and disease risk factors to promote health and prevent diseases. 12 Participants who did not have depression questionnaire data or sleep disorder data, or lack other information were excluded. This study did not need to be approved by the Institutional Review Board of the Affiliated Hospital of North Sichuan Medical College because the data was accessed from the NHANES (a publicly available database).…”
Section: Methodsmentioning
confidence: 99%
“…NHANES was conducted by the National Center for Health Statistics and Centers for Disease Control and Prevention, aiming at assessing the health status of the US population [ 18 ]. The interviews were performed by the study teams which were composed of medical and health technicians, multilingual physicians, and dietary health interviewers, and the information collected was designed to evaluate the incidence of major diseases and risk factors for diseases to promote health and prevent diseases [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a short, self-administered questionnaire, the Patient Health Questionnaire 9 (PHQ-9) is widely employed to screen depression in primary care settings [20]. Regarding the severity, depression was classified into five categories based on total PHQ-9 scores, including no depressive symptoms (0-4), mild depressive symptoms (5)(6)(7)(8)(9), moderate depressive symptoms (10)(11)(12)(13)(14), moderately severe depressive symptoms (15)(16)(17)(18)(19), and severe depressive symptoms (20)(21)(22)(23)(24)(25)(26)(27) [21]. In this study, depression was defined when the total PHQ-9 scores were equal to or greater than 10 [22].…”
Section: Data Sourcementioning
confidence: 99%
“…Poverty has been demonstrated to substantially increase the risk of infertility in many aspects: limited access to health services and nutrition increases susceptibility to genital infection ( 52 ). Moreover, a recent study based on 2005 to 2018 NHANES data reported that the prevalence of past-year marijuana use significantly increased among those with income below the poverty level ( 53 ). Marijuana use and poverty promote each other and may impair health and fertility.…”
Section: Discussionmentioning
confidence: 99%